Biokomposit Tenun dari Serat Daun Nanas dan Limbah Kulit Jeruk: Inovasi Material untuk Tekstil Berkelanjutan - Smaradhina, Ken Kayla; Widiawati, Dian (Jurnal Tekstil, 2025)
The growing urgency of sustainability in the textile industry necessitates the development of biodegradable materials derived from organic waste. This study introduces a composite material that integrates pineapple leaf fiber (PLF) with bioplastic made from orange peel waste, following the Material Driven Design (MDD) framework. The composite is produced through traditional weaving techniques (plain and twill) and cast using a gelatin–agar bioplastic matrix. Mechanical testing demonstrates tensile strength of up to 26.79 kg and elongation of 98.31%, depending on the PLF content and bioplastic thickness. User perception analysis indicates that samples combining twill weave with 300 ml of bioplastic provide the most desirable tactile and visual qualities. The resulting materials are biodegradable, locally sourced, and aesthetically engaging, positioning them as viable alternatives for accessories and interior products. This research contributes to sustainable material innovation by merging craft traditions with contemporary material experimentation.